Characteristic of the era of the Kazakh Khanate (Journal of history, 2019)
The author describes the presence of more than 20 states and tribalassociations that existed on the territory of Kazakhstan from ancient timesuntil the middle of the fifteenth century, which played an important rolein the process of formation of the Kazakh Khanate, as the author claimsthat the Kazakh Khanate is the legal successor of these states and tribalassociation.During the period of the Kazakh Khanate from the fifteenth centuryto the middle of the XVIII century, the author highlights the existence ofseveral stages of Khan’s . The author gives a brief description of each stage,and highlights their features. The author also dwells on the process of formation of the Kazakh Khanate. Thus, the author highlights the importanceof development of Khanate, in the context of the history of Kazakhstan